EGFR is required for FOS‐dependent bone tumor development via RSK2/CREB signaling - Markus Linder; Elisabeth Glitzner; Sriram Srivatsa; Latifa Bakiri; Kazuhiko Matsuoka; Parastoo Shahrouzi; Monika Dumanic; Philipp Novoszel; Thomas Mohr; Oliver Langer; Thomas Wanek; Markus Mitterhauser; et al. (EMBO Molecular Medicine)
Abstract Osteosarcoma (OS) is a rare tumor of the bone occurring mainly in young adults accounting for 5% of all childhood cancers. Because of the limited therapeutic options, there has been no survival improvement for OS patients in the past 40 years. The epidermal growth factor receptor (EGFR) is highly expressed in OS; however, its clinical relevance is unclear. Here, we employed an autochthonous c‐Fos‐dependent OS mouse model (H2‐c‐fosLTR) and human OS tumor biopsies for preclinical studies aimed at identifying novel biomarkers and therapeutic benefits of anti‐EGFR therapies. We show that EGFR deletion/inhibition results in reduced tumor formation in H2‐c‐fosLTR mice by directly inhibiting the proliferation of cancer‐initiating osteoblastic cells by a mechanism involving RSK2/CREB‐dependent c‐Fos expression. Furthermore, OS patients with co‐expression of EGFR and c‐Fos exhibit reduced overall survival. Preclinical studies using human OS xenografts revealed that only tumors expressing both EGFR and c‐Fos responded to anti‐EGFR therapy demonstrating that c‐Fos can be considered as a novel biomarker predicting response to anti‐EGFR treatment in OS patients.